The Security Council and the Repression of Maritime Piracy: The Case of Somalia - Maqsood, Safwan (Transactions on Maritime Science, 2020)
Maritime piracy in the Somali territorial waters has been the focus of attention of international society for at least twelve years, and indeed the crime of piracy threatens international peace and security in a region through which half of the world’s crude oil passes. In the three-decade absence of a Somali State, intervention by the Security Council is required to suppress such crimes and ensure freedom of maritime navigation. The Council resolutions based on Chapter VII of the UN Charter call for the Member States of the United Nations to arrest and bring to trial those accused of piracy before national courts. It is necessary for the States that are involved in anti-Somali piracy efforts to incorporate the principle of universal jurisdiction into their national laws and adopt new laws criminalizing modern piracy, which is outside the traditional notion of piracy stipulated in the United Nations Convention on the Law of the Sea 1982.